Antibacterial Activity Against Acne-Causing Bacteria and Compound Profiling of Bacteria Associated with the Black Gum Sea Cucumber (Holothuria leucospilota) - Novia Ashilia Arumawati; Isra Janatiningrum; Fitriyanti Fitriyanti; Vivi Anggia (Marine Science Department Diponegoro University, 2026)
Sea cucumbers (Holothuria leucospilota) have significant potential as sources of antibacterial compounds. These organisms live in association with bacteria that produce secondary metabolites exhibiting biological activities similar to those of their hosts, including antibacterial effects. Acne is an inflammatory condition that can be exacerbated by acne-causing bacteria such as Staphylococcus epidermidis and Propionibacterium acnes. Although antibiotics are commonly used for treatment, their effectiveness has increasingly been compromised by the emergence of antibiotic resistance. Bacteria associated with H. leucospilota therefore represent a promising alternative source of antibacterial agents due to their ability to produce bioactive secondary metabolites. This study aimed to characterize the macroscopic and microscopic diversity of these bacteria, evaluate their antibacterial activity against S. epidermidis and P. acnes, and analyze the chemical profiles of their ethyl acetate fractions. Bacterial isolation was conducted using Sea Water Complete Agar (SWCA), and antibacterial activity was assessed using the TLC bioautography method with iodonitrotetrazolium chloride (INT) as a growth indicator. A total of 12 bacterial isolates were obtained, comprising 10 isolates from the internal tissues and 2 isolates from the external surface of H. leucospilota. Antibacterial screening showed that 11 of the 12 isolates were active against S. epidermidis, while 8 isolates exhibited activity against P. acnes. Phytochemical screening indicated that phenolic and terpenoid compounds were the bioactive constituents responsible for the observed antibacterial activity.